DETERMINANTS OF CO₂ EMISSIONS IN THE SIX LARGEST CONTRIBUTING COUNTRIES: GDP, ENERGY, POPULATION, AND RENEWABLE ENERGY - Noubel Putra Nainggolan; Eko Wahyu Nugrahadi (JURNAL ECONOMICA : Research of Economic And Economic Education, 2026)
This study analyzes the effects of real Gross Domestic Product (GDP), per capita energy consumption, population, and renewable energy share on CO₂ emissions in the world’s six largest emitting countries China, the United States, India, Russia, Japan, and Indonesia over the period 2015-2024. The novelty lies in integrating the Environmental Kuznets Curve, Kaya Identity, Energy Intensity Theory, Energy Transition Theory, and Sustainable Development Theory into a single post-Paris Agreement panel data model. Using balanced panel data, the study selected the Random Effect Model (REM) through Chow, Hausman, and Lagrange Multiplier tests. Results indicate that real GDP (coef. = 0.000155; p = 0.0001), per capita energy consumption (coef. = 99,418.97; p = 0.0000), and population (coef. = 4.659; p = 0.0006) have a significant positive effect on CO₂ emissions. Renewable energy has a negative but insignificant effect (coef. = -9,321,612; p = 0.6578). Jointly, the four variables explain 75.38% of CO₂ emission variation (Adj. R² = 0.7538; F = 46.171; p = 0.0000). These findings imply that emission reduction requires simultaneous structural transformation across economic growth, energy use, demographic pressure, and genuine fossil-fuel substitution, not single-variable intervention.